1990
DOI: 10.1148/radiology.174.2.2404313
|View full text |Cite
|
Sign up to set email alerts
|

CT and MR imaging of intralabyrinthine schwannoma: report of two cases and review of the literature.

Abstract: Two cases of intralabyrinthine schwannoma were studied with computed tomography (CT) and magnetic resonance (MR) imaging. On CT scans, a soft-tissue mass was identified in the round window niche in both cases. Widening of the basilar turn of the cochlea and characteristic erosion of the promontory were noticed in one case. Preoperative MR imaging (performed in only one case) revealed a soft-tissue mass in the labyrnth, extending into the round window niche. Findings at CT and MR imaging are discussed, and a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Previous reports have proposed that the location on imaging may predict the symptoms. 10,[19][20][21] In earlier reports, it was suggested that tumors confined to the vestibule more commonly cause vertigo or symptoms similar to Meniere disease. 12,19,23 However, in our series, tumor location had no reproducible bearing on symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports have proposed that the location on imaging may predict the symptoms. 10,[19][20][21] In earlier reports, it was suggested that tumors confined to the vestibule more commonly cause vertigo or symptoms similar to Meniere disease. 12,19,23 However, in our series, tumor location had no reproducible bearing on symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, the first cases of ILS were globally described on enhanced MR imaging as homogeneous enhancement in the labyrinth. 10,27 Following this, several reports used enhanced MR imaging as a primary diagnostic tool for ILS. 12,14,16,17,22,23,26 More advanced imaging and characterization with high-resolution T2 and gradient recalled-echo sequences appeared in the literature in the early 2000s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Diagnosis of ILSs was difficult on CT, and only isolated cases were described. 5,6 With the advent of gadolinium (Gd)-enhanced MR imaging, an increasing number of ILSs were detected during screening for hearing loss and/or vertigo. 7 The use of heavily T2-weighted images for the detection of these lesions was reported a few years later.…”
mentioning
confidence: 99%